A Cost-effective 3D Printed Antibiotic Spacer for Management of Periprosthetic Joint Infection of the Knee: A Case Report. Issue 1 (March 2022) - Harna, Bushu; Kumar, Raj; Tomar, Shekhar; Meena, Abhay; Maini, Lalit
Abstract : Introduction: The 3-dimensional (D) printed customized bone cement spacer molds provide a single solution to various difficulties faced during the first stage of 2-stage exchange revision knee arthroplasty in periprosthetic joint infection. Materials and Methods: A 60-year-old lady presented with periprosthetic joint infection of the knee. The spacer molds were designed using computer-aided-design (CAD) software and intraoperatively antibiotic spacer was formed after assessing the bone gaps at a very low price ($100). Results: The infection was eradicated for over 3 months. The spacer was designed perfectly to the bone gaps and bone defects leading to proper gap balancing and wound closure. Conclusions: The CAD-articulating spacer helps to reduce the complexity of the surgical procedure. 3D printing provides a cost-effective measure to tackle such complex surgeries. The CAD-articulating spacer gives a futuristic guiding tool using 3D printing to make the surgery easier and more effective.